(untitled) (Revista Iberoamericana de Bioética, 2024)
The following work discusses therapeutic advances that involve modifications in human bodies. One of the main questions includes clinical trials, research subjects and the ability to decide. Ethical-communicational aspects in the relationship between researcher and research subject and doctor-patient will be analyzed. Should the possibility of an innovative treatment in which technologies that modify their organism be put into dialogue between researcher and research subject, or between doctor and patient? In turn, the specific cut of clinical trials in people deprived of liberty will be analyzed, taking as an analogy the fictional case of A Clockwork Orange to reflect on the autonomous decision in extreme circumstances from a bioethical perspective while we will try to respond to the question: Is the artificial modification of being an ethical way of solving social problems?